(untitled) (The Review of Diabetic Studies, 2025)
Road traffic accidents (RTAs) remain one of the leading causes of injury and death globally, particularly in low- and middle-income countries. Prehospital paramedic interventions play a crucial role in reducing morbidity and mortality by stabilizing trauma patients and ensuring timely transport to appropriate facilities. This systematic review analyzes evidence from 2015–2025 regarding the effectiveness of paramedic-led interventions in improving survival rates and patient outcomes following RTAs. Databases including PubMed, Scopus, and Web of Science were searched for randomized trials, observational studies, and meta-analyses addressing airway management, hemorrhage control, spinal immobilization, fluid resuscitation, and rapid transport systems. Findings indicate that early intervention by trained paramedics significantly reduces prehospital mortality, shortens scene-to-hospital time, and improves neurological recovery in severe trauma cases. The review highlights the need for standardized trauma protocols, continuous professional training, and technology-enabled communication between paramedics and trauma centers. Future research should focus on AI-assisted triage, simulation-based training, and region-specific outcome measurement, particularly within developing healthcare systems.